2013
DOI: 10.1039/c3ta00497j
|View full text |Cite
|
Sign up to set email alerts
|

In situ high temperature powder neutron diffraction study of undoped and Ca-doped La28−xW4+xO54+3x/2(x = 0.85)

Abstract: In situ neutron diffraction experiments of 2% Ca-doped and nominally undoped lanthanum tungstate (La 28Àx W 4+x O 54+3x/2 , with x ¼ 0.85) have been carried out under controlled pD 2 O and pO 2 at elevated temperatures. All the diffraction patterns could be refined using an average cubic fluorite-related structure, in accordance with recent reports. The material exhibits disorder of the oxygen and the cation sublattices. Splitting of the oxygen sites around tungsten from the 32f to 96k Wyckoff position in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 31 publications
5
53
1
Order By: Relevance
“…Combining these data results in a chemical expansion coefficient due to hydration, hydr , of 0.0088 per mol oxygen vacancy, which is much lower than that of the acceptor doped perovskites (see Section 5.1.1). Note that this value is only a lower limit for hydr , as the HT-ND data by Magrasó et al [252] may not be entirely at equilibrium at lower temperatures (≤400 °C). This is based on the shorter equilibration times used for their measurements (1-2 h), whereas Hancke et al [253] equilibrated their samples up to ~3.5 h at each temperature for their thermogravimetric analysis.…”
Section: Pyrochlore-and Fluorite-related Structuresmentioning
confidence: 75%
See 2 more Smart Citations
“…Combining these data results in a chemical expansion coefficient due to hydration, hydr , of 0.0088 per mol oxygen vacancy, which is much lower than that of the acceptor doped perovskites (see Section 5.1.1). Note that this value is only a lower limit for hydr , as the HT-ND data by Magrasó et al [252] may not be entirely at equilibrium at lower temperatures (≤400 °C). This is based on the shorter equilibration times used for their measurements (1-2 h), whereas Hancke et al [253] equilibrated their samples up to ~3.5 h at each temperature for their thermogravimetric analysis.…”
Section: Pyrochlore-and Fluorite-related Structuresmentioning
confidence: 75%
“…In terms of expansion, no quantitative study has determined the chemical expansion coefficient upon hydration for the lanthanum tungstates. However, we can estimate the coefficient using high temperature neutron diffraction (HT-ND) data on LWO56 (LWO where La/W = 5.6) by Magrasó et al [252], along with corresponding proton concentrations from TG data by Hancke et al [253]. The lattice parameter for LWO56 has been shown to increase by 0.14% upon hydration [252], while the proton concentration reaches an upper limit of 0.96 mol per mol oxide, that is, a hydration level where 66% of all oxygen vacancies (0.48 out of 0.73) in the structure hydrate [253].…”
Section: Pyrochlore-and Fluorite-related Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…5. LWO has three different cation sites, denoted La1, La2 and W. Combined experimental and theoretical calculations have revealed that 1/5 of the tungsten atoms in LWO reside on La2 sites [23,36]. Since the La2 sites are nearest neighbours both with W and La and form a continuous network for transport (cf.…”
Section: Bulk Diffusionmentioning
confidence: 98%
“…2 Substitution by alkaline-earth elements unexpectedly also leads to a reduction in conductivity, since these elements should act as acceptor dopants and increase the concentration of oxygen vacancies. 3,4,16,17 The authors may speculate that this behaviour could be attributed to stronger proton-acceptor association, as in other Ti-doped samples 18 , or to the fact that the compositions are metastable. 19 This point requires further work to be clarified.…”
Section: Introductionmentioning
confidence: 96%